Src family kinase oncogenic potential and pathways in prostate cancer as revealed by AZD0530 - Chang, Y-M (Oncogene, 2008)
Prostate cancer is the most frequently diagnosed cancer in American men. We have previously demonstrated that Src mediates androgen-independent proliferation in prostate cancer. We sought to investigate the Src-mediated oncogenic pathways and tumor biology using AZD0530, a novel Src family kinase/Abl dual-kinase inhibitor that is entering phase II clinical trials. We show that while both Src and Abl are expressed in all prostate cancer cell lines, Src but not Abl is activated in the prostate. Furthermore, Src activation is inhibited by AZD0530 in a rapid and dose-dependent manner. We show that Src mediates cell proliferation in DU145 and PC3 cells at the G1 phase of cell cycle. Src inhibition resulted in decreased binding of β-catenin to the promoters of G1 phase cell cycle regulators cyclin D1 and c-Myc. C-Myc may also be regulated at the protein level by extracellular signal-regulated kinase 1/2 and GSK3β. Cell motility factors focal adhesion kinase, p130CAS and paxillin activation in DU145 and PC3 cells were also inhibited. Administration of AZD0530 in mice reduced orthotopic DU145 xenograft growth by 45%. We have further delineated the Src-mediated oncogenic growth and migration pathways in prostate cancer and established mechanistic rationale for Src inhibition as novel therapy in the treatment of prostate cancer.